2004
DOI: 10.1063/1.1632552
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitrogen plasma on reactive-ion etching induced damage in GaN

Abstract: Lightly doped n-GaN samples were etched with reactive ion etching (RIE) in BCl3/Cl2/Ar and BCl3/Cl2/N2 plasmas. Replacing the argon by nitrogen in the plasma chemistry resulted in better etch rates, and in addition reduced etch damage for relatively low values of the plasma power. By treating the samples in a nitrogen plasma following etching, we dramatically reduced surface damage, as determined from Schottky IV characteristics measurements. Specifically, the reverse breakdown voltages returned to 70% to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Since the interface quality significantly affects the transistor performance, plasma‐assisted dry etching to form the recessed gate region and the subsequent formation of an insulator–semiconductor interface are critical steps for fabricating such devices. It has been reported that plasma‐assisted etching degrades the electrical and optical properties of GaN and AlGaN surfaces . Tang et al examined the SiO 2 /n‐GaN‐based capacitors and field‐effect transistors (FETs) fabricated on a Cl 2 ‐based inductively coupled plasma (ICP)‐etched GaN surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since the interface quality significantly affects the transistor performance, plasma‐assisted dry etching to form the recessed gate region and the subsequent formation of an insulator–semiconductor interface are critical steps for fabricating such devices. It has been reported that plasma‐assisted etching degrades the electrical and optical properties of GaN and AlGaN surfaces . Tang et al examined the SiO 2 /n‐GaN‐based capacitors and field‐effect transistors (FETs) fabricated on a Cl 2 ‐based inductively coupled plasma (ICP)‐etched GaN surface.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that plasma-assisted etching degrades the electrical and optical properties of GaN and AlGaN surfaces. [9][10][11][12] Tang et al 13) examined the SiO 2 /n-GaN-based capacitors and field-effect transistors (FETs) fabricated on the GaN surfaces etched by a Cl 2 -based inductively coupled plasma (ICP). They showed that ICP etching increased the interface state density and degraded the field-effect mobility of the FET channel.…”
mentioning
confidence: 99%
“…The dry etching process is commonly used for thinning AlGaN layers, in which the etching is carried out by applying plasma of an appropriate gas mixture containing a chemically reactive element. However, dry-etched surfaces tend to be negatively affected by various types of damage due to the bombardment of reactive ions and radicals [3,4]. These types of damage and defects induce high-density surface and interface states in the forbidden band, which leads to severe operational-stability problems such as gate leakage, current collapse, and Vth instability.…”
Section: Introductionmentioning
confidence: 99%